Internalization of Moderate Islamic Values in Education - Rahmat Kamal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2017)
This present study aims to investigate the essence and values of moderate Islam and internalize them in the process of education. The research findings are expected to be able to contribute a wide range of knowledge as one of alternatives to prevent and overcome symptoms of extreme and radical actions in students’ religious activities. It was a qualitative descriptive study by employing library research. This study highlights the imbalance between the concept of Islamic teachings demonstrating moderate values and the actions eroding the moderate Islamic values. Education plays a pivotal role to bring the image of peaceful Islam back by internalizing the moderate Islamic values in the process of education. The results reveal that (1) moderate Islam refers to a form of Islam that emphasizes the values of moderation between the ‘left-wing extremist group’ (liberal group) and the ‘right-wing extremist group’ (fundamental group) in implementing Islamic teachings; (2) moderate Islamic values include the values of tolerance in showing attitudes, the value of tolerance in respecting diversity, the value of inclusiveness in accepting something new with lots of strengths, the value of logic and flexibility in understanding texts, the value of relevance in interpreting texts by deeming their contexts, the value of innovation in solving problems that the answers have not been stated in the texts yet, and the value of social transformation; (3) the process of internalization covers three stages, namely: the stages of value transformation, value transaction, and trans-internalization. The first stage copes with the process that is carried out by teachers in informing the values of moderation conceptualized in Islamic teachings. The next stage promotes that the values of moderation are interactively communicated between teacher and students. The last stage suggests that familiarizing behavior and actions that represent the moderate Islamic values is performed through not only verbal communication, but also mentality and personality.